2011
DOI: 10.1002/pon.2029
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of Sense of Coherence Scale in women with cervical cancer

Abstract: The factor validity, predictive validity and divergent validity of C-SOC-13 were reasonable, as well as the internal consistency. In general, C-SOC-13 showed to be suitable as an SOC measurement for women with cervical cancer in Mainland China. However, SOC may have a different meaning to Chinese people because of the philosophy and culture that shape the context of their lives. Generalizing the findings to other populations requires further psychometric evaluation of C-SOC-13. Further longitudinal studies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
2
21
0
2
Order By: Relevance
“…Women who perceives higher response efficacy may have stronger beliefs about the screening benefits, and more likely to trust their physicians and uptake the recommended screening. This finding is of particularly significance for rural women in China because they lack the understanding of benefit effect for participating in screening prevention and are vulnerable to fatalistic views of cancer …”
Section: Discussionmentioning
confidence: 98%
“…Women who perceives higher response efficacy may have stronger beliefs about the screening benefits, and more likely to trust their physicians and uptake the recommended screening. This finding is of particularly significance for rural women in China because they lack the understanding of benefit effect for participating in screening prevention and are vulnerable to fatalistic views of cancer …”
Section: Discussionmentioning
confidence: 98%
“…Few studies of SOC and dental health have been conducted in Chinese populations since the C-SOC-13 scale was created [26,27], and no study has addressed SOC and oral health-related behaviors. Thus, the manner in which SOC influences Chinese health behaviors demands further research.…”
Section: Discussionmentioning
confidence: 99%
“…Since the anchors of each item are different, a short instrument is warranted, particularly from a feasibility point of view. The psychometric properties of the SOC-13 have primarily been evaluated with classical statistical methods (i.e., Cronbach’s alpha, inter-item correlation and factor analysis) and in general populations of students [14] and active older people, as well as patients with chronic illnesses such as cancer [15] or cardiac disease [16]. The studies have generally concluded that the SOC-13 is a reliable and valid instrument.…”
Section: Introductionmentioning
confidence: 99%